2010
DOI: 10.1002/jmri.22392
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma associated with Xp11.2 translocation/TFE3 gene fusion: Radiological findings mimicking papillary subtype

Abstract: The authors describe the computed tomography (CT) and magnetic resonance imaging (MRI) findings of an 18-yearold man with renal cell carcinoma (RCC) associated with the Xp11.2 translocation/transcription factor E3 (TFE3) gene fusion (Xp11 translocation carcinoma). The lesion was hyperdense on unenhanced CT, hypovascular on contrast-enhanced studies, hypointense on T2-weighted MR images, and hemosiderin deposition was suspected on phase-shift gradient-echo MR images. Histopathological specimens revealed patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
8
29
0
Order By: Relevance
“…On contrast enhanced study of CT, however, it showed heterogeneous enhancement. No particular enhancement pattern of Xp11.2 RCC is reported yet, however, thick peripheral rim enhancement was noted in the previous report, which was similar to our case (9). There was mild and delayed enhancement in the periphery of the lesion in our case and this is believed to be caused by partial capsule formation .…”
Section: Index Words : Renal Cell Carcinoma•xp112 Translocation•tfe3supporting
confidence: 87%
See 1 more Smart Citation
“…On contrast enhanced study of CT, however, it showed heterogeneous enhancement. No particular enhancement pattern of Xp11.2 RCC is reported yet, however, thick peripheral rim enhancement was noted in the previous report, which was similar to our case (9). There was mild and delayed enhancement in the periphery of the lesion in our case and this is believed to be caused by partial capsule formation .…”
Section: Index Words : Renal Cell Carcinoma•xp112 Translocation•tfe3supporting
confidence: 87%
“…Our study showed a low ADC value in the tumor, especially in the peripheral portion (1.043 × 10 -3 mm 2 /sec). However, DWI of Xp11.2 RCC in a previous report was isointense compared with renal parenchyma (9). Further study is needed to refine this aspect.…”
Section: Index Words : Renal Cell Carcinoma•xp112 Translocation•tfe3mentioning
confidence: 75%
“…On plain CT, most of these tumors showed iso-attenuation or slight hyper-attenuation compared to the normal renal cortex. Such hyper-attenuation is thought to be due to hemorrhagic or proteinaceous fluid, densely packed cellular components, or a combination of these factors [13], [16]. MRI provided important information on the tumor parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Citations of articles used in the table: Argani et al 2007 Rais-Bahrami et al 2007 LaGrange et al 2007 Franzini et al 2007 Hora et al 2008 Camparo et al 2008 Hora et al 2009 Suarez-Vilela et al 2011, Koie et al 2009 Armah et al 2009 Kuroda et al 2010 Choueiri et al 2010 Ishihara et al 2011 Liu et al 2011 Nelius et al 2011 Numakura et al 2011, Kato et al 2011 Klatte et al 2012 Morii et al 2012 Rao et al 2012 Inamura et al 2012 Arnoux et al 2012 Komai et al 2009 Gaillot-Durand et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…In some previous studies data on the radiological features (CT and MRI) of Xp11 TRCC have been presented. These have failed to identify any specific radiological features of this tumour Liu et al 2013;Koo et al 2013; Kato et al 2011). …”
Section: Discussionmentioning
confidence: 99%